Bilytska V. M. Lexical features of the german social and political texts based on the videoreport materials - Bilytska V. M. (Philological Treatises, 2020)
According to the current research, it should be pointed out that video reports as socio-political texts play a significant role in the work of a translator and teacher, and in the process of studying of a foreign language by a student, since the media actually serves as the main medium of the global socio-political communication. Working with lexical units of actual socio-political texts in the process of studying a foreign language, teaching it and in translation work is not only desirable, but also necessary under the present conditions. The study of the features of the use of certain lexical units in the video reports texts will not only create a basis for working with such texts in the process of teaching foreign languages, but also will open new perspectives for further research in the field of teaching methods of foreign languages. This work will also be interesting in the context of pre-translation analysis of the text for the effective preparation of future translators and for the work of already trained specialists.